2002
DOI: 10.1128/aem.68.8.4025-4034.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Phaseolus -Nodulating Rhizobial Populations Is Altered by Liming of Acid Soils Planted with Phaseolus vulgaris L. in Brazil

Abstract: PCR-mediated restriction fragment length polymorphism (RFLP) analysis of the 16S-23S rRNA internally transcribed spacer (ITS) region and the 16S rRNA gene indicated that the rhizobial populations isolated from common bean (Phaseolus vulgaris L.) nodules in the unlimed soil from a series of five lime rates applied 6 years previously to plots of an acidic oxisol had less diversity than those from plots with higher rates of liming. Isolates affiliated with Rhizobium tropici IIB and Rhizobium leguminosarum bv. pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 35 publications
2
39
1
8
Order By: Relevance
“…In the present study, the physiological characterization showed a high tolerance of the strains COL6, CB1 and SOS1 to grow at different pH values, salinity conditions and temperatures. Similar results reported by Andrade, Murphy and Giller (2002) and Shamseldin and Werner (2005) as well as the predominant R. tropici, which nodulates P. vulgaris in southern Ecuador (Table 4). Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country.…”
Section: Resultssupporting
confidence: 86%
“…In the present study, the physiological characterization showed a high tolerance of the strains COL6, CB1 and SOS1 to grow at different pH values, salinity conditions and temperatures. Similar results reported by Andrade, Murphy and Giller (2002) and Shamseldin and Werner (2005) as well as the predominant R. tropici, which nodulates P. vulgaris in southern Ecuador (Table 4). Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country.…”
Section: Resultssupporting
confidence: 86%
“…This result may explain the presence of the species R. tropici (LBMP-4BR) in a soil with corn monoculture in minimum tillage (Table 1). However, Andrade et al (2002) observed a predominance of R. leguminosarum in acid soils that were not treated with lime. This is similar to results found in this study, as LBMP-3VE was isolated from acidic soil with no lime application.…”
Section: Resultsmentioning
confidence: 97%
“…Vegetative forms of bacteria multiply in the infection threads and saprophytic zones of indeterminate type nodules, and are released into the soil during the decay of nodules [4,5]. Amongst the heterogeneous microbial communities in the soil, rhizobia constitute numerous and very differentiated populations [6][7][8][9][10]. Several factors can influence the number and diversity of indigenous rhizobia, including nutrient availability, soil type, acidity and agricultural management regimes [6,11,12].…”
Section: Introductionmentioning
confidence: 99%